Formate can differentiate between hyperhomocysteinemia due to impaired remethylation and impaired transsulfuration. - MOLLOY, ANNE (My University, 2012)
Formate can differentiate between hyperhomocysteinemia due to impaired remethylation and impaired transsulfuration. Am J Physiol Endocrinol Metab 301: E000-E000, 2011. First published September 20, 2011; 10.1152/ajpendo.00345.2011.-We carried out a (1)H-NMR metabolomic analysis of sera from vitamin B(12)-deficient rats. In addition to the expected increases in methylmalonate and homocysteine (Hcy), we observed an approximately sevenfold increase in formate levels, from 64 μM in control rats to 402 μM in vitamin B(12)-deficient rats. Urinary formate was also elevated. This elevation of formate could be attributed to impaired one-carbon metabolism since formate is assimilated into the one-carbon pool by incorporation into 10-formyl-THF via the enzyme 10-formyl-THF synthase. Both plasma and urinary formate were also increased in folate-deficient rats. Hcy was elevated in both the vitamin B(12)- and folate-deficient rats. Although plasma Hcy was also elevated, plasma formate was unaffected in vitamin B(6)-deficient rats (impaired transsulfuration pathway). These results were in accord with a mathematical model of folate metabolism, which predicted that reduction in methionine synthase activity would cause increased formate levels, whereas reduced cystathionine β-synthase activity would not. Our data indicate that formate provides a novel window into cellular folate metabolism, that elevated formate can be a useful indicator of deranged one-carbon metabolism and can be used to discriminate between the hyperhomocysteinemia caused by defects in the remethylation and transsulfuration pathways
PUBLISHED
Keywords: hyperhomocysteinemia; hyperhomocysteinemia